The interaction systems generated by the teacher’s didactic imprinting - Peralta, Nadia S. (2015)
The current study aimed to identify and analyze the systems of interaction implemented by teachers in university classes, based on their teaching imprints. It focused on the interactions occurred in scholar natural contexts and the construction of knowledge based on said interaction. A form to observe the different behaviors was designed in order to register the interaction during practical sessions. Six classes and their teachers, from two different epistemic areas (Psychology and Physics), were observed, and the results were analyzed in order to describe the characteristics of the classes and the type of interactions that take place in them. Based on a global qualitative analysis of the classes, three basic types of interaction were detected: collaborative, guided participative and expositive. Beyond the characteristics detected, it is stated that no matter the interaction system, teachers aim to increase the students’ knowledge in all cases.